(untitled) (Journal of Oriental Studies, 2016)
Introduction of new profession-oriented training programmes gave rise to communicative competence formation at English lessons. Reading of authentic professional literature in a foreign language is one of the ways of achieving this goal. Particular emphasis is given to various activities used at the lessons.